Evaluative decision task performance as a measure of automatic evaluation of affective stimuli - Rebernjak, Blaž (Array, 2013)
This study deals with measurement of individual differences in automatic processing of affective stimuli within affective priming paradigm. The paradigm used was employed to ope rationalize the individual differences in automatic evaluation. The automatic processing measures, termed processing tendencies, were defined by parcels composed of difference score items of the Evaluative Decision Task reaction time variables. SOA of 150ms was used to keep the strategic processing to the minimum. A total of 186 students participated in the study. Confirmatory factor analytic framework was used to examine the structure of relationships among processing tendencies and to test the stability of individual differences in a four week period.